EMIC triggered chorus emissions in Cluster data. Issue 3 (28th March 2013) - Grison, B.; Santolík, O.; Cornilleau‐Wehrlin, N.; Masson, A.; Engebretson, M. J.; Pickett, J. S.; Omura, Y.; Robert, P.; Nomura, R.
<x xml:space="preserve">Abstract</x> [1] Electromagnetic ion cyclotron (EMIC) triggered chorus emissions have recently been a subject of several experimental, theoretical and simulation case studies, noting their similarities with whistler‐mode chorus. We perform a survey of 8 years of Cluster data in order to increase the database of EMIC triggered emissions. The results of this is that EMIC triggered emissions have been unambiguously observed for only three different days. These three events are studied in detail. All cases have been observed at the plasmapause between 22 and 24 magnetic local time (MLT) and between − 15∘ and 15∘ magnetic latitude (λm). Triggered emissions are also observed for the first time below the local He+ gyrofrequency <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sp8znqw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />fHe+</alternatives>. The number of events is too low to produce statistical results, nevertheless we point out a variety of common properties of those waves. The rising tones have a high level of coherence and the waves propagate away from the equatorial region. The propagation angle and degree of polarization are related to the distance from the equator, whereas the slope and the frequency extent vary from one event to the other. From the various spacecraft separations, we determine that the triggering process is a localized phenomenon in space and time. However, we are unable to determine the occurrence rates of these waves. Small frequency extent rising tones are more common than large ones. The newly reported EMIC triggered events are generally observed during periods of large AE index values and in time periods close to solar maximum.